A pre-filtration PTFE modified separation membrane and its preparation method and application
By introducing a hydrophilic layer on the surface of the PTFE separation membrane and modifying it with organic bentonite, the problem of insufficient hydrophilicity on the surface of the PTFE filter membrane and poor arsenic filtration effect was solved, and efficient arsenic removal and membrane purification effects were achieved.
Patent Information
- Application Number
- CN202411215943.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-19
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-02
AI Technical Summary
The surface of existing PTFE filter membranes is insufficiently hydrophilic, resulting in poor filtration of arsenic in water, and the surface of the membrane is easily contaminated by organic matter and protein, affecting flux.
By introducing a hydrophilic layer on the surface of the PTFE separation membrane and modifying it with materials such as organic bentonite and phenyl ketone, a dynamic adsorption and separation integrated technology is formed to improve the hydrophilicity and adsorption capacity of the membrane.
It achieves effective filtration and removal of arsenic in water, improves the purification capacity and anti-pollution performance of the membrane, and at the same time enhances the mechanical strength and flux of the membrane.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to a membrane separation material surface hydrophilic modification technology, in particular to a pre-filtration PTFE modified separation membrane and a preparation method thereof. Background Art
[0002] Membrane separation technology has been widely used in the fields of water purification, regeneration, and reuse due to its good selectivity, energy saving, high efficiency, good pollution resistance, and easy integration. It has become one of the common technical supports for solving today's environmental problems, and membrane separation technology has been valued worldwide. Industrial and domestic water also includes some groundwater, but the removal of arsenic has always been a difficult point, especially for arsenic removal by membrane filtration. Arsenic usually needs to be treated in multiple stages and multiple times, such as by reduction replacement or precipitation, which have great limitations, especially for arsenic removal from flowing water, which is difficult to achieve with existing technologies.
[0003] Membrane is the key to membrane separation technology, which directly determines the accuracy and efficiency of separation. It mainly includes organic membrane, inorganic membrane and inorganic / organic composite membrane. Polytetrafluoroethylene (PTFE) is the main type of fluororesin and is a polymer with excellent physical and chemical properties. PTFE can be divided into fiber membrane, flat membrane and tubular membrane according to the configuration of membrane components. Compared with flat membrane, tubular membrane and other separation membrane forms, PTFE filter membrane has become the main form of microfiltration and ultrafiltration membrane process due to its higher component filling density and excellent mechanical self-support. It is currently widely used in food, medicine, fermentation, chemical industry, electronics, domestic water and sewage treatment and other fields.
[0004] PTFE is a membrane separation material with excellent comprehensive performance. It has excellent chemical stability, heat resistance, cold resistance and chemical corrosion resistance. At the same time, it also has good electrical insulation, low surface tension and friction coefficient, non-flammability, atmospheric aging resistance, high and low temperature adaptability and high mechanical properties. It has broad application prospects in the field of membrane separation. However, due to the low surface energy and strong hydrophobicity of this type of membrane material, when treating the aqueous phase separation system, the mass transfer driving force of the fluid through the membrane is high, the energy consumption is large, and the water flux is low; in addition, the hydrophobic membrane surface is very easy to adsorb impurities such as organic matter and protein, resulting in concentration polarization, causing the membrane to be seriously contaminated, resulting in a sharp drop in flux. These shortcomings restrict the further promotion and application of PTFE. Modifying the surface of PTFE filter membrane, introducing a hydrophilic layer on its surface, and combining the excellent properties of PTFE itself is a simple and effective method to expand the use of poly-PTFE separation membranes. With the continuous expansion of the application scope of PTFE filter membrane, various methods for hydrophilic modification are available, mainly including surface plasma treatment, surface graft polymerization, surface chemical treatment and surface coating. Patent document with application number CN03804097.2 discloses a chemical surface modification method of polytetrafluoroethylene material, which reduces the fluorine content on the surface of polytetrafluoroethylene material and improves the hydrophilicity of the material surface by using a modifier and irradiation treatment; reduces the fluorine content on the surface of polytetrafluoroethylene material and improves the hydrophilicity of the material surface by using a modifier and irradiation treatment; Chinese invention patent application CN200610154892.6 discloses a method containing The method for hydrophilizing the surface of fluoropolymer separation membrane is to pre-irradiate the surface of polytetrafluoroethylene membrane with high-energy rays, generate active free radicals on the surface of the membrane, and initiate graft polymerization of hydrophilic functional monomers on the membrane surface to improve the hydrophilicity of the membrane surface; US Patent No. 4113912 discloses coating a hydrophilic polymer such as polyvinyl alcohol, polyethylene oxide or polyacrylic acid on the surface of fluoropolymer material, and then cross-linking the hydrophilic polymer by heat treatment, acetalization or esterification to form a hydrophilic layer on the surface of fluoropolymer material; US Patent No. 5630941 improves the hydrophilicity of fluoropolymer by coating a thin layer of polymer electrolyte on the surface of fluoropolymer. These modification methods have their own characteristics. In comparison, surface modification often damages the structure of the membrane surface to a certain extent, especially surface plasma treatment and surface chemical etching, and there are certain uncertainties in the modification process; simple surface physical coating cannot obtain a lasting hydrophilic modification effect; in addition, due to the chemical inertness of polytetrafluoroethylene material, its modification process is relatively complicated and the effect is poor. Therefore, it is necessary to develop an efficient, stable and economical method for hydrophilizing the surface of polytetrafluoroethylene membranes. However, the current PTFE filter membranes cannot effectively filter arsenic in water, and most PTFE filter membranes have almost no filtering effect on arsenic in solution.
[0005] PTFE filter membranes are widely used in many industrial fields such as air and water purification due to their good chemical stability, high strength, low friction, corrosion resistance, low surface energy and excellent hydrophobic properties, and have received widespread attention worldwide.
[0006] Due to the special pore structure and stable physical and chemical properties of PTFE filter membrane, its application prospects are very broad. However, there are still many difficulties in the processing of PTFE filter membrane, such as free control of micropore diameter, increasing porosity, improving pore structure, etc. In order to expand its application field, the use of reasonable and effective surface modification methods is also an urgent problem to be solved. With the continuous deepening of research, exploring the best preparation process and modification method of PTFE filter membrane has a broader room for development. Summary of the invention
[0007] In order to solve the problems of limited surface tension, poor wetting performance and inability to effectively filter arsenic in water in existing PTFE filter membranes, the present invention provides a pre-filtration PTFE modified separation membrane and a preparation method of the PTFE modified separation membrane.
[0008] The purpose of the present invention is: 1. To realize a PTFE separation membrane which can be used for filtering and can effectively remove arsenic.
[0009] 2. Improve the adsorption capacity of PTFE separation membrane and enhance its role in purifying domestic water.
[0010] 3. Improve the hydrophilicity of the PTFE separation membrane surface.
[0011] Fourth, adjusting the processing fluidity of the membrane-forming composition, and at the same time adjusting the membrane pore structure and the permeability of the membrane pores of the formed separation membrane.
[0012] To achieve the above objectives, the present invention adopts the following technical solutions.
[0013] A method for preparing a pre-filtration PTFE modified separation membrane comprises: (1) preparing a raw material containing PTFE resin, adding an alkane organic matter and mixing them uniformly to obtain a precursor membrane.
[0014] (2) The precursor film is heated, and organic bentonite is added to perform sintering, stretching, and secondary sintering to obtain a PTFE crude film.
[0015] (3) Add the mixed liquid to organically modify the PTFE crude membrane to obtain a pre-filtration PTFE modified separation membrane.
[0016] Preferably, the raw materials in step (1) are PTFE resin, 1-phenylbutan-1-one, and hexafluorobenzene; the content of 1-phenylbutan-1-one is 10-15 wt%, the content of hexafluorobenzene is 3-7 wt%, and the rest is PTFE resin; the alkane organic matter in step (1) is 2-methylisododecane; the 2-methylisododecane is added in an amount of 15-20 wt% of the total mass of the PTFE resin used in the raw materials.
[0017] Preferably, the heating process in step (2) is to place the precursor film at 150-200° C. for 3-7 min.
[0018] Preferably, the organic bentonite in step (2) is bentonite modified with hexadecyl dimethyl ferric bromide; the amount of the bentonite modified with hexadecyl dimethyl ferric bromide is 20 to 30 wt% of the total mass of the raw materials.
[0019] Preferably, the hexadecyl dimethyl ferric bromide modified bentonite is prepared by mixing bentonite and hexadecyl dimethyl ferric bromide. The bentonite and hexadecyl dimethyl ferric bromide are uniformly mixed in a mass ratio of 1: (0.8-1.2), left to stand for 25-35 minutes, and then ground to 100-200 meshes to obtain the hexadecyl dimethyl ferric bromide modified bentonite.
[0020] Preferably, the sintering in step (2) is carried out at 280-320°C for 1-3 min to soften the film and / or slightly melt the film on its surface; the stretching in step (2) is carried out at 200-300°C, with a stretching ratio of 150-300%; and the secondary sintering in step (2) is carried out at 180-230°C for 2-5 min.
[0021] Preferably, the mixed solution is a mixed solution of sodium naphthalene solution, hydrogen peroxide and sulfuric acid solution; the sodium naphthalene solution, hydrogen peroxide and sulfuric acid solution are mixed in a mass ratio of 1: (0.3-0.6): (0.4-0.6); the sodium naphthalene solution is a 0.95-1.05 mol / L sodium naphthalene tetrahydrofuran solution; the concentration of the sulfuric acid solution is 60-70 wt%.
[0022] Preferably, the organic modification in step (3) is carried out at a temperature of 90 to 120° C. for 10 to 30 min.
[0023] A pre-filtration PTFE modified separation membrane.
[0024] The invention discloses an application of a pre-filtration PTFE modified separation membrane, wherein the pre-filtration PTFE modified separation membrane is used for pre-filtration of heavy metal elements; in the pre-filtration process, the liquid to be filtered passes through 1 to 3 layers of the pre-filtration PTFE modified separation membrane at a flow rate of 6 to 8 mm / s.
[0025] There are strong hydrogen bonds between water molecules, which are the main binding force between water molecules. In the technical solution of the present invention, the separation membrane is connected to carboxyl and hydroxyl hydrophilic groups, so that there are a large number of hydrogen bonds on the surface of the separation membrane, which can provide hydrogen atoms for the formation of hydrogen bonds. Because there are lone pairs of electrons on the oxygen atoms in the polar functional groups, they can accept hydrogen atoms provided by other molecules and form hydrogen bonds with the lone pairs of electrons and hydrogen ions on the oxygen atoms between water molecules. At the same time, since hydrogen bonds with similar structures are formed between the separation membrane of the external groups and the water molecules, the affinity of the separation membrane to water is improved.
[0026] In the technical solution of the present invention, the core lies in adding organic bentonite to the separation membrane material, realizing dynamic adsorption and separation integrated technical treatment, improving the hydrophilicity of the surface of the PTFE filter membrane, and adjusting the processing fluidity of the film-forming composition. According to the research of the inventor, bentonite can effectively adsorb various suspended particles in the water environment and has a good adsorption effect. However, since the powdered bentonite is easily swollen to form a dispersed suspended mud after being soaked in water, the sedimentation performance is poor, resulting in very difficult solid-liquid separation, which greatly restricts the application in water treatment. Therefore, in the technical solution of the present invention, hexadecyl dimethyl ferric bromide is used to modify bentonite, and phenyl ketone is cross-linked with the PTFE composite membrane as a supporting layer to prevent the filtration unit from being blocked, so that the trapped suspended impurities and the separation membrane can be easily detached during backwashing, thereby solving the problem of difficult solid-liquid separation of bentonite. At the same time, during the thermal reorganization process of the sintered separation membrane, due to the transfer of energy and structural reorganization, the electrons bound near the atoms and some freely moving cations appear in a superposition state, forming quasiparticles in the filtration unit. Whenever the quasiparticle state appears, the adsorption effect of the cations in the water by the filtration unit will be enhanced. When the number of free-moving cations is much larger than the fixed electrons, the quasiparticles will collapse and disappear, and the impurities adsorbed on the membrane and the metal complexes on the membrane surface will be impacted and separated from the membrane surface, thereby coupling the two operating units of adsorption and separation into one, and realizing dynamic adsorption and separation integrated technology.
[0027] In the technical solution of the present invention, organic bentonite is added during the separation membrane formation process to make the membrane-forming composition system have appropriate processing fluidity. The addition of isoalkanes can further adjust the processing fluidity of the membrane-forming composition and adjust the membrane pore structure and membrane pore permeability of the formed separation membrane.
[0028] In PTFE, fluorine atoms replace hydrogen atoms in polyethylene. Since the volume of fluorine atoms is larger, with a radius of 0.064nm, which is larger than that of hydrogen atoms (0.028nm), and the negative charges of fluorine atoms in adjacent macromolecules repel each other, the CC chain gradually twists from the planar, fully stretched zigzag conformation of polyethylene to the helical conformation of PTFE, and forms a tight, completely "fluorinated" protective layer, which gives the material great chemical stability and low cohesive energy density. The bond energy of CC bond is 372KJ / mol, and the bond energy of CF bond is 347 KJ / mol, which is the stronger bond energy among the known bonds. Therefore, the intramolecular bond is strong and heat-resistant. The long-term use temperature is -250~260℃, and the bond length of CC bond is 1.54×10 10 m, the bond length of the CF bond is 1.41×10 10 m, which is the shortest among the common single pieces, so the chemical properties are stable, showing excellent weather resistance, stain resistance and chemical resistance. The main chain of the macromolecule is chemically modified, and the whole internal cross-linking is formed, which increases the attraction and surface energy between PTFE molecules. Therefore, PTFE has a higher surface friction coefficient, so that the separation membrane will not slide during use, causing the separation membrane to shift, thereby reducing the separation membrane filtration efficiency.
[0029] In the technical solution of the present invention, another core point is that the PTFE modified separation membrane is subjected to three heat treatments to form a special spatial composition, strengthen the peeling strength, increase the air permeability of the separation membrane, and make the pore size distribution of the separation membrane uniform. In order to further improve the strength of the separation membrane, the PTFE separation membrane is subjected to a heating post-treatment, the purpose of which is to melt the resin on the surface of the PTFE particles, improve the bonding strength between the PTFE particles, and complete the degreasing treatment of the PTFE composite membrane. The purpose of the first sintering is to build a metal organic framework inside the PTFE material. Under high temperature conditions, by selectively breaking the CF bonding CH bond and activating the adsorption of bentonite, the metal organic framework built inside the PTFE material is composed of iron as a metal node and a porous crystal composed of PTFE. In particular, the iron ligands in the solid surface complex and the trivalent arsenic and pentavalent arsenic in the solution can be removed simultaneously. The trivalent arsenic is catalyzed to pentavalent arsenic that is easily adsorbed on the surface of the separation membrane. The filtration unit on the surface of the separation membrane produces a large number of active adsorption sites such as surface hydroxyls, so that the pentavalent arsenic adsorbs arsenic according to the ligand exchange principle. When the quasi-particles collapse and separate, the electron layer is subjected to energy shock to form a complex with bentonite, which is separated from the water body in the form of precipitation. At the same time, it is continuously subjected to energy shock, so that the complex is accumulated away from the membrane body. The purpose of the second sintering is to stabilize the metal organic framework, fix the filtration unit, and form a porous structure inside the membrane. In the technical scheme of the present invention, the complex free radicals generated by the interaction between metallic sodium and naphthalene are mixed with H2O2 and H2SO4 to generate active oxygen, which promotes the defluorination of the molecular structure on the surface of the PTFE composite membrane, links the carboxyl and hydroxyl polar groups, introduces polar functional groups on the PTFE surface, and reacts with the sodium naphthalene solution with the PTFE material to destroy the CF bond on the surface of the membrane material and connect the carboxyl and hydroxyl hydrophilic groups, so that the hydrophilicity of the PTFE material is improved. At the same time, under the activation of the active oxygen, the wettability of the pores and surface of the PTFE composite membrane with the hydrophilic polymer is improved, a stable spatial structure is built, and the formation of the filtration unit is promoted. Under the cross-linking action of the quaternary ammonium salt, an in-situ cross-linking reaction is carried out in the membrane pores and on the surface, and a uniform and stable cross-linked polymer hydrophilic layer is formed in the membrane pores and on the surface, which greatly simplifies the hydrophilic modification process of the PTFE filter membrane surface, and can significantly improve the hydrophilicity of the membrane surface. At the same time, a large number of active adsorption sites such as surface hydroxyl groups are generated, so that the separation membrane can remove pentavalent arsenic in the water body by ligand exchange, and accelerate the morphological transformation and interface transfer of arsenic on the oxidation and adsorption micro-interfaces.After high-temperature modification and stretching, a microporous film is formed. The film has a small pore size, uniform distribution, and high porosity. While maintaining the circulation of water, it can filter all dust particles including bacteria, thereby achieving the purpose of pre-treating the water. At the same time, in the metal organic framework filtration unit built inside the PTFE material in the technical solution of the present invention, due to the interaction between sodium and naphthalene and the cross-linking effect of quaternary ammonium salts, there are a large number of active adsorption sites inside the filtration unit, which can effectively induce and pull the metal ions lead, zinc and cadmium in the water to form complexes with organic bentonite, so that the metal ions are separated from the water and undergo in-situ cross-linking reactions in the membrane pores and the filtration unit. The hydrophilic PTFE micropores in the solution of the present invention have excellent biological safety and high temperature resistance, large flux, high strength, and no shedding at high temperature. It is suitable for filtration of strong acid and strong alkaline solutions, terminal sterilization filtration of liquid medicines, high-temperature liquid filtration, water treatment, and environments where other filtration materials are not competent.
[0030] By using the method of multiple sintering in the technical solution of the present invention, a PTFE porous composite membrane can be obtained, while overcoming the shortcomings of dense membrane skin and high processing temperature usually caused by the sintering method, using PTFE melt-bonded organic bentonite particles, no high-temperature sintering forming is required, low-temperature forming can be achieved, and the composite membrane is given strong hydrophilicity, and the obtained separation membrane has low protein adsorption and high pollution resistance. The metal organic framework constructed by the present invention is evenly distributed in the porous composite membrane, and heavy metal ions and arsenic ions in the water system are removed by forming a coordinated molecular cage. The porous material of the metal organic framework has unique molecular properties, wherein relatively isolated filtering units can effectively adsorb other doping substances dispersed in the water system, and the coordinated molecular cage can realize various supramolecular framework connections and strengthen the stability of the complex when used as a solid material, and can also generate intermolecular forces between different complexes, so that the precipitate will not dissolve in the water system again, achieving the effect of efficient arsenic removal.
[0031] Advantages of the present invention: (1) The present invention modifies the PTFE filter membrane, which can effectively improve the hydrophilicity of the membrane surface and is used for filtering and removing arsenic in water.
[0032] (2) The hydrophilic modified polymer used in the present invention is widely available and has low cost.
[0033] (3) The technical solution provided by the present invention has a simple production process and is suitable for industrial production. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0035] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0036] Unless otherwise specified, the average particle size of the PTFE resin used in the embodiments of the present invention is ≥350 μm.
[0037] Unless otherwise specified, the purity of 1-phenylbutan-1-one used in the examples of the present invention is 99 wt %.
[0038] Unless otherwise specified, the purity of hexafluorobenzene used in the embodiments of the present invention is 98 wt %.
[0039] Unless otherwise specified, the purity of 2-methylisododecane used in the examples of the present invention is 99 wt %.
[0040] Example 1: A method for preparing a pre-filtration PTFE modified separation membrane, the method comprising: (1) taking 10-15 wt% of 1-phenylbutan-1-one, 3-7 wt% of hexafluorobenzene, and the rest being PTFE resin, adding 15 wt% of 2-methylisododecane based on the total mass of the PTFE resin, stirring and mixing at room temperature, and compression molding at a pressure of 5 Mpa to obtain a precursor membrane.
[0041] (2) The precursor film was kept warm at 150 °C for 3 min, bentonite and hexadecyl dimethyl ferric bromide were mixed in a mass ratio of 1:0.8 and allowed to stand for 30 min to obtain an organic modified bentonite, the organic modified bentonite was ground to a particle size of 100 mesh, 20 wt% of the total amount of the raw materials of the organic modified bentonite was evenly spread on both sides of the precursor film, and the film was kept warm at 280 °C for 1 min to soften it, and stretched at 200 °C with a stretching ratio of 150%, and then kept warm at 180 °C for 2 min to obtain a PTFE crude film.
[0042] (3) A mixture of sodium naphthalene solution, H2O2 and sulfuric acid solution was prepared in a ratio of 1:0.3:0.4, and the mixture was added to the PTFE crude membrane and kept at 90°C for 10 min to obtain a pre-filtered PTFE modified separation membrane; the sodium naphthalene solution was a 0.95 mol / L sodium naphthalene tetrahydrofuran solution, and the concentration of the sulfuric acid solution was 60 wt%.
[0043] The prepared separation membrane was subjected to performance testing, and the specific testing steps and characterization results are as follows: Testing of the separation membrane filtration effect of inorganic heavy metals: Soluble lead salts, zinc salts, cadmium salts and deionized water were used to prepare standard test solutions with Pb content of 0.50 mg / L, Zn content of 0.50 mg / L and Cd content of 0.50 mg / L. The standard test solution was passed through the prepared separation membrane at a flux of 8 mm / s for 4 hours. The inorganic heavy metal content of the filtered solution was tested and recorded every 1 hour. The characterization results are shown in Table 1.
[0044] Table 1: Characterization results of inorganic heavy metal filtration test in Example 1:
[0045] Characterization results: Detection of arsenic removal effect of separation membrane: Soluble arsenic salt and deionized water were used to prepare standard test solution A with an As(III) content of 0.05 mg / L, standard test solution B with an As(V) content of 0.05 mg / L, and standard test solution C with an As(III) content of 0.03 mg / L and an As(V) content of 0.03 mg / L. The standard test solutions were passed through the prepared pre-filtered PTFE modified separation membrane at a flux of 8 mm / s for 2 h, and the arsenic content of the filtered solutions was characterized and recorded.
[0046] Membrane flux test: Use membrane materials to separate two independent airflow systems, one side is flowing oxygen, and the other side is flowing dry nitrogen. The oxygen side has a higher partial pressure. The concentration difference drives the oxygen to pass through the membrane and is sent to the sensor by the nitrogen flow. The sensor accurately measures the amount of oxygen carried in the nitrogen flow, and thus calculates the oxygen permeability of the material. The oxygen permeability directly measured by the sensor method and uncorrected, the calculation formula for oxygen permeability provided by ISO 15105-2 is: , the recording unit is converted to mm / s (0.1MPa test condition).
[0047] Elongation at break test: Using a tensile testing machine, pull the film at a speed of 200 mm / min, and calculate the strength (the value obtained by dividing the tensile load by the cross-sectional area of the sample) and the elongation when the film sample is torn. The calculation formula for elongation at break is as follows.
[0048] Elongation at break (%) = 100 × (L-Lo) / Lo.
[0049] Lo: Sample length before testing.
[0050] L: sample length when torn.
[0051] The characterization results are shown in Table 2.
[0052] Table 2: Characterization results of arsenic filtration, membrane flux and elongation at break of Example 1:
[0053] Characterization: Liquid A is the standard test liquid A, liquid B is the standard test liquid B, and liquid C is the standard test liquid C.
[0054] From the above characterization results, the pre-filtered PTFE modified separation membrane of the present invention can effectively filter and remove arsenic, and the removal rate of trivalent arsenic reaches more than 65%, and the removal rate of pentavalent arsenic reaches more than 80%. For the situation where trivalent arsenic and pentavalent arsenic exist at the same time, the comprehensive removal rate can also reach more than 75%, which can effectively realize the arsenic removal pretreatment of water body. After groundwater exploitation, the PTFE modified separation membrane of the present invention can effectively filter and remove solid particulate impurities, and pre-treat to reduce the arsenic content in the water body. At the same time, the PTFE modified separation membrane of the present invention also has relatively good membrane flux and elongation at break performance.
[0055] Example 2: A method for preparing a pre-filtration PTFE modified separation membrane. (1) Take 13 wt% of 1-phenylbutan-1-one, 5 wt% of hexafluorobenzene, and the rest is PTFE resin, add 17 wt% of 2-methylisododecane based on the total mass of the PTFE resin, stir and mix evenly at room temperature, and then mold at a pressure of 5 MPa to obtain a precursor membrane.
[0056] (2) The precursor film was kept warm at 150 °C for 5 min, bentonite and hexadecyl dimethyl ferric bromide were mixed in a mass ratio of 1:1 and allowed to stand for 30 min to obtain an organic modified bentonite, the organic modified bentonite was ground to a particle size of 150 mesh, 25 wt% of the total amount of the raw material of the organic modified bentonite was evenly spread on both sides of the precursor film, and the temperature was kept at 280 °C for 1 min to soften it, and the film was stretched at 200 °C with a stretching ratio of 200%, and then kept warm at 200 °C for 2 min to obtain a PTFE crude film.
[0057] (3) A mixture of sodium naphthalene solution, H2O2 and sulfuric acid solution was prepared in a ratio of 1:0.5:0.5, and the mixture was added to the PTFE crude membrane and kept at 100°C for 20 min to obtain a pre-filtered PTFE modified separation membrane; the sodium naphthalene solution was a 1.0 mol / L sodium naphthalene tetrahydrofuran solution, and the concentration of the sulfuric acid solution was 65 wt%.
[0058] The prepared separation membrane was subjected to performance testing, and the specific testing steps and characterization results are as follows: Testing of the inorganic heavy metal filtration effect of separation membrane: Soluble lead salt, zinc salt, cadmium salt and deionized water were used to prepare standard test solutions with Pb content of 0.50 mg / L, Zn content of 0.50 mg / L and Cd content of 0.50 mg / L. The standard test solution was passed through the prepared separation membrane at a flux of 8 mm / s for 4 hours. The inorganic heavy metal content of the filtered solution was tested and recorded every 1 hour. The characterization results are shown in Table 3.
[0059] Table 3: Characterization results of inorganic heavy metal filtration test in Example 2:
[0060] Detection of arsenic removal effect of separation membrane: Soluble arsenic salt and deionized water were used to prepare standard test solution A with an As(III) content of 0.05 mg / L, standard test solution B with an As(V) content of 0.05 mg / L, and standard test solution C with an As(III) content of 0.03 mg / L and an As(V) content of 0.03 mg / L. The standard test solutions were passed through the prepared pre-filtered PTFE modified separation membrane at a flux of 8 mm / s for 2 h, and the arsenic content of the filtered solutions was characterized and recorded.
[0061] Membrane flux test: Use membrane materials to separate two independent airflow systems, one side is flowing oxygen, and the other side is flowing dry nitrogen. The oxygen side has a higher partial pressure. The concentration difference drives the oxygen to pass through the membrane and is sent to the sensor by the nitrogen flow. The sensor accurately measures the amount of oxygen carried in the nitrogen flow, and thus calculates the oxygen permeability of the material. The oxygen permeability directly measured by the sensor method and uncorrected, the calculation formula for oxygen permeability provided by ISO 15105-2 is: , the recording unit is converted to mm / s (0.1MPa test condition).
[0062] Elongation at break test: Using a tensile testing machine, pull the film at a speed of 200 mm / min, and calculate the strength (the value obtained by dividing the tensile load by the cross-sectional area of the sample) and the elongation when the film sample is torn. The calculation formula for elongation at break is as follows.
[0063] Elongation at break (%) = 100 × (L-Lo) / Lo.
[0064] Lo: Sample length before testing.
[0065] L: sample length when torn.
[0066] The characterization results are shown in Table 4.
[0067] Characterization: Liquid A is the standard test liquid A, liquid B is the standard test liquid B, and liquid C is the standard test liquid C.
[0068] Table 4: Characterization results of arsenic filtration, membrane flux and elongation at break of Example 2:
[0069] Judging from the above characterization results, it also has good arsenic removal ability and good basic mechanical properties.
[0070] Example 3: A method for preparing a pre-filtration PTFE modified separation membrane. (1) Take 15 wt% of 1-phenylbutan-1-one, 7 wt% of hexafluorobenzene, and the rest is PTFE resin, add 20 wt% of 2-methylisododecane based on the total mass of the PTFE resin, stir and mix evenly at room temperature, and then mold at a pressure of 5 MPa to obtain a precursor membrane.
[0071] (2) The precursor film was kept warm at 200 °C for 7 min, bentonite and hexadecyl dimethyl ferric bromide were mixed in a mass ratio of 1:1.2 and allowed to stand for 30 min to obtain an organic modified bentonite, the organic modified bentonite was ground to a particle size of 100 mesh, 30 wt% of the total amount of the raw material of the organic modified bentonite was evenly spread on both sides of the precursor film, and the temperature was kept at 280 °C for 1 min to soften it, and the film was stretched at 200 °C with a stretching ratio of 300%, and then kept warm at 230 °C for 5 min to obtain a PTFE crude film.
[0072] (3) A mixture of sodium naphthalene solution, H2O2 and sulfuric acid solution in a ratio of 1:0.6:0.6 was prepared, and the mixture was added to the PTFE crude membrane and kept at 120°C for 30 min to obtain a pre-filtered PTFE modified separation membrane; the sodium naphthalene solution was a 1.05 mol / L sodium naphthalene tetrahydrofuran solution, and the concentration of the sulfuric acid solution was 70 wt%.
[0073] The performance of the prepared separation membrane was tested, and the specific test steps and characterization results are as follows: Test on the effect of separation membrane in filtering inorganic heavy metals: Soluble lead salt, zinc salt, cadmium salt and deionized water were used to prepare standard test solutions with Pb content of 0.50 mg / L, Zn content of 0.50 mg / L and Cd content of 0.50 mg / L. The standard test solution was passed through the prepared separation membrane at a flux of 8 mm / s for 4 hours. The inorganic heavy metal content of the filtered solution was tested and recorded every 1 hour. The characterization results are shown in Table 5.
[0074] Table 5: Characterization results of inorganic heavy metal filtration test in Example 3:
[0075] Detection of arsenic removal effect of separation membrane: Soluble arsenic salt and deionized water were used to prepare standard test solution A with an As(III) content of 0.05 mg / L, standard test solution B with an As(V) content of 0.05 mg / L, and standard test solution C with an As(III) content of 0.03 mg / L and an As(V) content of 0.03 mg / L. The standard test solutions were passed through the prepared pre-filtered PTFE modified separation membrane at a flux of 8 mm / s for 2 h, and the arsenic content of the filtered solutions was characterized and recorded.
[0076] Membrane flux test: Use membrane materials to separate two independent airflow systems, one side is flowing oxygen, and the other side is flowing dry nitrogen. The oxygen side has a higher partial pressure. The concentration difference drives the oxygen to pass through the membrane and is sent to the sensor by the nitrogen flow. The sensor accurately measures the amount of oxygen carried in the nitrogen flow, and thus calculates the oxygen permeability of the material. The oxygen permeability directly measured by the sensor method and uncorrected, the calculation formula for oxygen permeability provided by ISO 15105-2 is: , the recording unit is converted to mm / s (0.1MPa test condition).
[0077] Elongation at break test: Using a tensile testing machine, pull the film at a speed of 200 mm / min, and calculate the strength (the value obtained by dividing the tensile load by the cross-sectional area of the sample) and the elongation when the film sample is torn. The calculation formula for elongation at break is as follows.
[0078] Elongation at break (%) = 100 × (L-Lo) / Lo.
[0079] Lo: Sample length before testing.
[0080] L: sample length when torn.
[0081] The characterization results are shown in Table 6.
[0082] Table 6: Characterization results of arsenic filtration, membrane flux and elongation at break of Example 3:
[0083] Characterization: Liquid A is the standard test liquid A, liquid B is the standard test liquid B, and liquid C is the standard test liquid C.
[0084] Judging from the above characterization results, it also has good arsenic removal ability and good basic mechanical properties.
[0085] Comparative Example 1: A method for preparing a pre-filtration PTFE modified separation membrane, the specific preparation method of which is the same as that of Example 2, except that the unique organic bentonite of the present invention is changed, and water-soluble lithium nitrate and sodium chloride are used instead of hexadecyl dimethyl ferric bromide to prepare the separation membrane. The specific operation is as follows: (1) Take 13 wt% of 1-phenylbutan-1-one, 5 wt% of hexafluorobenzene, and the rest is PTFE resin, add 17 wt% of 2-methyl isododecane based on the total mass of the PTFE resin, stir and mix evenly at room temperature, and then mold it at a pressure of 5 Mpa to obtain a precursor membrane.
[0086] (2) The precursor film was kept warm at 150 °C for 5 min, bentonite was mixed with lithium nitrate and sodium chloride in a mass ratio of 1:0.5:0.5, and the mixture was allowed to stand for 30 min to obtain an organic modified bentonite, the organic modified bentonite was ground to a particle size of 150 mesh, 25 wt% of the total amount of the raw material of the organic modified bentonite was evenly spread on both sides of the precursor film, and the mixture was kept warm at 280 °C for 1 min to soften it, and stretched at 200 °C with a stretching ratio of 200%, and then kept warm at 200 °C for 2 min to obtain a PTFE crude film.
[0087] (3) A mixture of sodium naphthalene solution, H2O2 and sulfuric acid solution was prepared in a ratio of 1:0.5:0.5, and the mixture was added to the PTFE crude membrane and kept at 100°C for 20 min to obtain a pre-filtered PTFE modified separation membrane; the sodium naphthalene solution was a 1.0 mol / L sodium naphthalene tetrahydrofuran solution, and the concentration of the sulfuric acid solution was 65 wt%.
[0088] The same characterization as in Example 2 was performed, and the characterization results are shown in Table 7.
[0089] Table 7: Test results of the inorganic heavy metal filtration effect of separation membrane in comparative example 1.
[0090]
[0091] The test results of the arsenic removal effect of the separation membrane are shown in Table 8.
[0092] Table 8: Characterization results of arsenic filtration, membrane flux and elongation at break of Comparative Example 1:
[0093] Characterization: Liquid A is the standard test liquid A, liquid B is the standard test liquid B, and liquid C is the standard test liquid C.
[0094] By comparing the above characterization results with Example 2, it is found that the added inorganic additives can also form larger holes on the membrane wall, and can form connected and through pores to obtain more effective through-membrane separation pores, thereby obtaining a high-flux separation membrane. However, the addition of inorganic additives will lead to the degradation of the stability of the membrane. Although it can be observed that the membrane flux and elongation at break have been improved, when hexadecyl dimethyl ferric bromide is replaced by lithium nitrate and sodium chloride, the separation membrane basically loses the ability to filter trivalent arsenic. It can be inferred that although the organic modified bentonite has a significant optimization effect on the arsenic removal ability of the PTFE modified separation membrane, it has a certain influence on the mechanical properties of the PTFE modified separation membrane.
[0095] Comparative Example 2: A method for preparing a pre-filtration PTFE modified separation membrane, wherein the specific preparation method is the same as that of Example 2, except that the organic bentonite unique to the present invention is not used, and the separation membrane is prepared. The specific operations are as follows: (1) 13 wt% of 1-phenylbutan-1-one, 5 wt% of hexafluorobenzene and 17 wt% of 2-methylisododecane are added to PTFE resin, stirred for 40 min at a temperature of 23°C to mix evenly, and then molded at a pressure of 5 Mpa to form a precursor membrane.
[0096] (2) The precursor film was heated at 175 °C for 5 min, and the first sintering temperature was 300 °C for 2 min. The melting ratio of the precursor film material was 33 wt%. It was stretched at 250 °C with a stretching ratio of 200%. Then, the second sintering temperature was 200 °C for 4 min to obtain a PTFE crude film.
[0097] (3) A mixture of sodium naphthalene solution, H2O2 and sulfuric acid solution was kept warm at 100 °C for 20 min for surface modification, wherein the sodium naphthalene solution was a 1.0 mol / L sodium naphthalene tetrahydrofuran solution, and the concentration of the sulfuric acid solution was 65%. The sodium naphthalene solution, H2O2 and sulfuric acid solution were mixed in a ratio of 1:0.5:0.5 to form an organically modified PTFE composite membrane to obtain a pre-filtration PTFE modified separation membrane.
[0098] The same characterization as in Example 2 was performed, and the characterization results are shown in Table 9.
[0099] Table 9: Test results of the inorganic heavy metal filtration effect of separation membrane in comparative example 2.
[0100]
[0101] The test results of arsenic removal effect of separation membrane are shown in Table 10.
[0102] Table 10: Characterization results of arsenic filtration, membrane flux and elongation at break of Comparative Example 2:
[0103] Analyzing the above characterization results, compared with Example 2, it is found that adding organic bentonite during the separation membrane formation process not only plays a role in swelling the internal structure of the PANI material, but also makes the film-forming composition system have appropriate processing fluidity, adjusts the membrane pore structure and the permeability of the membrane pores of the formed separation membrane, and at the same time, the metal organic framework built inside the PTFE material is formed by iron as a metal node and PTFE / PANI to form a solid surface complex. The iron ligands and trivalent arsenic and pentavalent arsenic in the solution can be removed synchronously, and trivalent arsenic is catalyzed on the surface of the separation membrane to be easily adsorbed pentavalent arsenic. The filtration unit on the surface of the separation membrane produces a large number of active adsorption sites such as surface hydroxyl groups, so that pentavalent arsenic is adsorbed according to the ligand exchange principle. At the same time, it also proves the phenomenon of comparative example 1, and the organic modified bentonite used in the present invention has a certain influence on the mechanical properties of the PTFE modified separation membrane.
[0104] The researchers believe that this may be because the use of organic bentonite causes the PTFE-modified separation membrane to form some kind of agglomeration nodes at the microscopic level, which makes it easy for stress concentration to occur when the membrane is subjected to force, and then the membrane breaks.
[0105] Comparative Example 3: A method for preparing a pre-filtration PTFE modified separation membrane. The specific preparation method is the same as that in Example 2, except that the unique sintering method of the present invention is changed to prepare the separation membrane. The specific operations are as follows: (1) Take 13 wt% of 1-phenylbutan-1-one, 5 wt% of hexafluorobenzene, and the rest is PTFE resin, add 17 wt% of 2-methylisodecane based on the total mass of the PTFE resin, stir and mix evenly at room temperature, and then mold it at a pressure of 5 Mpa to obtain a precursor membrane.
[0106] (2) The precursor film was kept warm at 150 °C for 5 min, bentonite and hexadecyl dimethyl ferric bromide were mixed in a mass ratio of 1:1 and allowed to stand for 30 min to obtain an organic modified bentonite, the organic modified bentonite was ground to a particle size of 150 mesh, 25 wt% of the total amount of the raw material of the organic modified bentonite was evenly spread on both sides of the precursor film, and stretched at 250 °C with a stretching ratio of 200%, and sintered for 10 min to obtain a PTFE crude film.
[0107] (3) A mixture of sodium naphthalene solution, H2O2 and sulfuric acid solution was kept warm at 100 °C for 20 min for surface modification, wherein the sodium naphthalene solution was a 1.0 mol / L sodium naphthalene tetrahydrofuran solution, and the concentration of the sulfuric acid solution was 65%. The sodium naphthalene solution, H2O2 and sulfuric acid solution were mixed in a ratio of 1:0.5:0.5 to form an organically modified PTFE composite membrane to obtain a pre-filtration PTFE modified separation membrane.
[0108] The same characterization as in Example 2 was performed, and the characterization results are shown in Table 11.
[0109] Table 11: Test results of the inorganic heavy metal filtration effect of separation membrane in comparative example 3.
[0110]
[0111] The test results of arsenic removal effect of separation membrane are shown in Table 12.
[0112] Table 12: Characterization results of arsenic filtration, membrane flux and elongation at break of Comparative Example 3:
[0113] By analyzing the above characterization results and comparing them with Example 2, it is found that the first sintering builds a metal organic framework inside the PTFE material and activates the adsorption of bentonite, strengthening the membrane's filtration of arsenic in water, and the second sintering stabilizes the metal organic framework, fixes the filtration unit, forms a porous structure inside the membrane, and strengthens the mechanical properties of the membrane material. It can be seen that the sintering process has a great influence on the core arsenic removal performance and mechanical properties of the PTFE modified separation membrane prepared by the present invention, mainly because the reaction of the membrane at the microscopic level is difficult to effectively control during the sintering process.
[0114] Comparative Example 4: A commercially available polytetrafluoroethylene composite nanofiltration membrane (PTFE nanofiltration membrane) was subjected to the same characterization as in Example 2. The characterization results are shown in the following table.
[0115] The test results of the separation membrane filtration effect of inorganic heavy metals are shown in Table 13.
[0116] Table 13: Comparative Example 4 Inorganic Heavy Metal Filtration Test Characterization Results:
[0117] The test results of arsenic removal effect of separation membrane are shown in Table 14.
[0118] Table 14: Characterization results of arsenic filtration, membrane flux and elongation at break of Comparative Example 4:
[0119] It can be clearly seen from the analysis of the above characterization results that the commercially available PTFE nanofiltration membrane basically has no ability to filter and remove arsenic, and does not have the effect of effectively filtering and removing heavy metal ions, but in terms of permeability and mechanical strength, it is far superior to the PTFE modified separation membrane prepared by the technical solution of the present invention.
[0120] Continuous arsenic filtration test: A continuous filtration test was carried out using the pre-filtration PTFE modified separation membrane prepared in Example 2. Standard test solution A with an As(III) content of 0.05 mg / L, standard test solution B with an As(V) content of 0.05 mg / L, and standard test solution C with an As(III) content of 0.03 mg / L and an As(V) content of 0.03 mg / L were prepared using soluble arsenic salts and deionized water. The standard test solutions were passed through 3 layers of the pre-filtration PTFE modified separation membrane prepared in Example 2 at a flux of 8 mm / s, with a spacing of 15 cm between each layer of the pre-filtration PTFE modified separation membrane. The test was continued for 2 h, and the effluent was sampled and characterized.
[0121] The characterization results are shown in Table 15.
[0122] Table 15: Continuous arsenic filtration test characterization results:
[0123] From the above characterization results, it can be seen that the pre-filtration PTFE modified separation membrane prepared by the present invention has an extremely low filtration threshold, and can very effectively filter and remove arsenic ions in water bodies. The use of the modified separation membrane of the present invention for single-layer filtration treatment can achieve pre-filtration treatment of water bodies and greatly reduce the arsenic content in the water bodies. After multi-layer membrane treatment, it can even directly and effectively reduce the arsenic content in the water body to a safe range. It has a very good filtration limit and shows a very excellent filtration and arsenic removal ability. It can be very effectively used for pre-filtration treatment of domestic water and pre-filtration treatment of arsenic removal of industrial water.
[0124] However, in subsequent experiments, it was found that when the number of membrane layers was further increased, the effect of filtration and refining was difficult to further effectively improve, and it might cause the pressure difference between membranes to increase, resulting in a weakening of the filtration effect. Therefore, from a comprehensive consideration of cost and effect, the use of 1 to 3 layers of membranes, especially using 1 layer of membrane as a simple pre-filtration and 3 layers of membranes for deep pre-filtration, is relatively the best.
[0125] Continuous heavy metal filtration test: A continuous filtration test was carried out using the pre-filtration PTFE modified separation membrane prepared in Example 2. A standard test solution with a Pb content of 0.50 mg / L, a Zn content of 0.50 mg / L, and a Cd content of 0.50 mg / L was prepared using soluble lead salts, zinc salts, cadmium salts and deionized water. The standard test solution was passed through 3 layers of the pre-filtration PTFE modified separation membrane prepared in Example 2 at a flux of 8 mm / s. The spacing between each layer of the pre-filtration PTFE modified separation membrane was 15 cm. The test was continued for 4 hours, and the effluent was sampled and characterized.
[0126] The characterization results are shown in Table 16.
[0127] Table 16: Continuous heavy metal filtration test characterization results:
[0128] From the above characterization results, it can be seen that the pre-filtration PTFE modified separation membrane prepared by the present invention can effectively remove heavy metal ions in water bodies, and a single-layer modified separation membrane can realize filtration pretreatment of the target water body, and can filter out a large amount of heavy metal ions. After multi-layer filtration, the heavy metal ion content in the water body can meet the sanitary standards for drinking water in my country. As pointed out in GB 5749-2022, the limit index of As is 0.01 mg / L, the limit index of Pb is 0.01 mg / L, the limit index of Zn is 1.0 mg / L, and the limit index of Cd is 0.005 mg / L. The membrane material of the present invention can meet the limit standards after multi-layer filtration of the water body, reflecting excellent filtration performance, and can be very effectively used for pre-filtration treatment of domestic water and pre-filtration treatment of industrial water.
Claims
1. A method for preparing a pre-filtration PTFE modified separation membrane, characterized in that: The method comprises: (1) preparing a raw material containing PTFE resin, adding an alkane organic matter and mixing them evenly to obtain a precursor film; (2) heating the precursor film, adding organic bentonite for sintering, stretching, and secondary sintering to obtain a PTFE crude film; (3) adding the mixed liquid to organically modify the PTFE crude membrane to obtain a pre-filtration PTFE modified separation membrane; The organic bentonite in step (2) is bentonite modified by hexadecyl dimethyl ferric bromide; The amount of the bentonite modified by hexadecyl dimethyl ferric bromide is 20-30 wt% of the total mass of the raw materials; The hexadecyl dimethyl ferric bromide modified bentonite is prepared by mixing bentonite and hexadecyl dimethyl ferric bromide. The bentonite and hexadecyl dimethyl ferric bromide are uniformly mixed in a mass ratio of 1: (0.8-1.2), and the mixture is allowed to stand for 25-35 minutes and then ground to 100-200 meshes to obtain the hexadecyl dimethyl ferric bromide modified bentonite. The mixed solution is a mixed solution of sodium naphthalene solution, hydrogen peroxide and sulfuric acid solution; The sodium naphthalene solution, hydrogen peroxide and sulfuric acid solution are mixed in a mass ratio of 1: (0.3-0.6): (0.4-0.6); The sodium naphthalene solution is a 0.95-1.05 mol / L sodium naphthalene tetrahydrofuran solution; The concentration of the sulfuric acid solution is 60-70 wt %.
2. The method for preparing a pre-filtration PTFE modified separation membrane according to claim 1, characterized in that: The raw materials in step (1) are PTFE resin, 1-phenylbutan-1-one, and hexafluorobenzene; The 1-phenylbutan-1-one content is 10 to 15 wt %, the hexafluorobenzene content is 3 to 7 wt %, and the rest is PTFE resin; The alkane organic compound in step (1) is 2-methylisododecane; The 2-methyl isododecane is added in an amount of 15 to 20 wt % of the total mass of the PTFE resin used in the raw material.
3. The method for preparing a pre-filtration PTFE modified separation membrane according to claim 1, characterized in that: The heating process in step (2) is to place the precursor film at 150-200°C for 3-7 minutes.
4. The method for preparing a pre-filtration PTFE modified separation membrane according to claim 1, characterized in that: The sintering in step (2) is performed at 280-320°C for 1-3 min to soften the material and / or slightly melt the surface of the material; The stretching in step (2) is carried out at 200-300°C, and the stretching ratio is controlled to be 150-300%; The secondary sintering in step (2) is carried out at a temperature of 180 to 230° C. for 2 to 5 minutes.
5. The method for preparing a pre-filtration PTFE modified separation membrane according to claim 1, characterized in that: The organic modification in step (3) is carried out at a temperature of 90 to 120° C. for 10 to 30 minutes.
6. A pre-filtration PTFE modified separation membrane prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method of chemical surface modification of polytetrafluoroethylene materials
CN100345871C
Surface hydrophilicity modification process for separating fluoric polymer film
CN1986038A
Hydrophilic porous structures and process for production thereof
US4113912A
Permanent hydrophilic modification of fluoropolymers
US5630941A
Pre-filtering PTFE modified separation membrane and preparation method thereof
CN118512935A